Metabolomic Signatures Influenced by Different Cardioplegic Solutions in Cardiac Surgery - Chananya Karunasumetta; Chotika Chatgasem; Suriya Punchai; Kittisak Sawanyawisuth (Journal of the Practice of Cardiovascular Sciences)
Introduction: Cardioplegia is crucial for myocardial protection during cardiac surgery. However, the impact of different cardioplegia formulations on patients’ metabolomic responses has not been explored. The objective is to identify unique metabolomic signatures associated with each cardioplegia type and evaluate their potential correlations with clinical outcomes. Methods: A prospective cohort study was conducted from January 2023 to June 2024, involving 105 samples from 21 patients undergoing isolated coronary artery bypass graft with modified del Nido, Custodiol®, or St. Thomas cardioplegia. Pre- and postoperative plasma samples were collected for analysis of cardiac enzyme levels and proton nuclear magnetic resonance metabolomic profiling. Results: No significant differences in clinical outcomes or cardiac enzyme levels were observed between the groups. However, distinct pre-and postoperative metabolomic profiles were identified. The Custodiol group exhibited significant postoperative metabolomic changes within the first 2 days, with nine differentially expressed metabolites (DEMs). In contrast, modified del Nido cardioplegia affected three DEMs on postoperative day 0, whereas St. Thomas showed no alteration in the postoperative metabolomic profile. These DEMs were associated with protein and energy production, oxidative stress, and inflammatory responses. Key differential metabolites between the groups included histidine and alanine, which notably impacted the histidine metabolism pathway. Conclusion: The findings demonstrate that distinct cardioplegia solutions result in differential postoperative metabolomic alterations, with Custodiol exhibiting the most pronounced shifts, whereas St. Thomas cardioplegia showed no significant postoperative metabolic changes.